UJI AKTIVITAS ANTIOKSIDAN SEDIAAN TEH HERBAL DARI KULIT BUAH NAGA MERAH (HYLOCEREUS POLYRHIZUS) DAN KULIT KAYU MANIS (CINNAMOMUM BURMANII) - Yulia Yesti; Miming Andika; Harry Ade Saputra; Oryza Sativa Fitriani; Shantrya Dhelly Susanti; Fahira Azlaini Burma (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Indonesia is a plant-producing country, especially in the tropics of Indonesia there are 30,000 plant species. Of these, there are 9,600 plant species that are useful as medicine, but 200 species have been used as raw materials for the herbal industry for health, one of which is from red dragon fruit skin (Hylocereus polyrhizus). This type of research is experimental research. This research was conducted qualitatively and quantitatively which was carried out from July-August 2022. The data obtained in this study were used to determine the antioxidant content of herbal tea preparations in red dragon fruit skin (Hylocereus polyrhizus) and cinnamon bark (Cinnamomum burmani) and for data analysis, the data obtained was tested linear regression using the SPSS v16 program. to obtain a linear equation, so that the value of antioxidant activity (IC50) is obtained. Data analysis was continued with the one way ANOVA method (ANOVA). So it can be concluded that the herbal tea preparations of red dragon fruit skin (Hylocereus polyrhizus) and cinnamon bark (Cinnamomum burmanii) in the antioxidant test had a good temperature at 80OC (45.123 ppm) because based on IC50 because the lower the IC50 value, the stronger the IC50 value. The IC50 value is the effective concentration of an antioxidant substance capable of inhibiting the activity of a free radical by 50%. For the IC50 value for the combination tea of red dragon fruit skin and cinnamon bark at 60OC (47.605 ppm) and 100OC (48.585 ppm). Where free radicals are very good at heating temperatures of 80OC. The results showed that the heating temperature of herbal tea simplicia had an effect on the antioxidants produced in each sample. It can be concluded that from the 3 differences in heating temperature variations, the antioxidant yield was very good at 80OC with an IC50 result of 45.123 ppm. Further research needs to be done with the manufacture of dragon fruit peel and cinnamon bark herbal tea in the form of dyes so that the presentation is faster, easier and more practical. Further research is needed to determine the shelf life of dragon fruit peel and cinnamon herbal tea products.Keywords: Red Dragon Fruit Peel, Cinnamon Bark Herbal Tea Preparation.